Effect of soil burial on mechanical properties of bamboo fiber reinforced epoxy composites - Chin, Siew Choo; Tong, F. S.; Doh, Shu Ing; Lim, Kar Sing; Jolius, Gimbun (IOP Publishing, 2020)
Nowadays, natural fiber reinforced composites in structural strengthening and rehabilitation was preferable due to its environmentally friendly, low cost and biodegradable characteristics compared to the synthetic strengthening material, fiber reinforced polymer (FRP). However, limited information is available on natural fiber composite durability when exposed to environmental elements. This paper presents the effect of environmental exposure to the durability of bamboo fiber reinforced epoxy composite. Bamboo fiber reinforced epoxy composite samples were prepared and buried in soil for 20, 40, 60 and 80 days. The composite samples were prepared using 40% fiber volume fractions. The mechanical properties (tensile and flexural) and surface morphology of the samples before and after degradation were investigated. The experimental results show that the mechanical properties deteriorate as the exposure time increases. The tensile and flexural properties of the composites decreased by about 6-19% compared to the fresh sample. The result from this work may be useful to determine the durability of natural fiber composite when exposed to environmental elements.